Peran Pengasuh dalam Meningkatkan Kemampuan Diri Anak Untuk Mengontrol Kemandirian Diri di Panti Asuhan Hanifah III Kampung - Nur Afni Wijaya; Fadhilla Yusri (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Orphanages are institutions that shape the growth and development of children who do not have parents or for some reason do not live with their families. An orphanage is a house, a place (a place to live), while an orphanage is a house where orphaned children are cared for and nurtured and so on. Article 55 paragraph (3) of Law of the Republic of Indonesia Number 23 of 2002 explains that in relation to the implementation of the care and maintenance of neglected children, state institutions and community institutions can cooperate with various parties as referred to in paragraph 2. Orphanage is defined as a house, place or residence where orphans, orphans, and orphaned children are cared for (taken care of). In an orphanage there is a caregiver who educates, nurtures, protects and provides comfort to the children in his care. Caregivers are foster parents who are respected and appreciated by their foster children.